Using the Stochastic Geometry and Characteristics Method for Modeling and Analysis of Interference in Automotive Radar - Ghadir Madi; Khawla Hamwi; Mary Titizian (Tishreen University, 2020)
Automotive radar systems are an important technology that offers intelligent and independent features in modern vehicles to improve road traffic safety. Due to the next large deployment of radar technology, a significant increase in (radar-radar) interference has expected, resulting in lower performance. This paper addresses the issue of mutual interference between automotive radars resulting from the shared spectrum use and  real critical road scenarios. First, we built a model of a real system that simulates the geometrical design of vehicles flowing on the highway, depending on the stochastic geometry of the Poisson point process model with density  . Then, we used the LWR (Lighthill Whitham Richards) characteristic curves to find the distribution function of traffic density at different time intervals of the studied road. Later, we formed a mathematical formula to calculate the mean interference value at different time intervals of the road. The system has tested using MATLAB program. At the end of the research, we were able to demonstrate the effectiveness of the characteristics method in predicting the distribution function of traffic density, and hence the knowledge of temporal behavior of the interference, especially in real road scenarios. تُعتبر أنظمة رادار السيّارات تقنية هامّة تقدّم ميّزات ذكية ومُستقلّة في السيّارات الحديثة من أجل تحسين السلامة المرورية على الطرق. على الرغم من أهمّية هذه الأنظمة، إلى أنّها تُعاني من مُشكلة تداخل (رادار- رادار) ممّا يؤدّي إلى انخفاض أداؤها. يتناول هذا البحث مسألة التداخل المُتبادل بين رادارات السيّارات الناتج عن الاستخدام المُشترك للطيف والسيناريوهات الحقيقية الحرجة على الطرق. بدايةً، قُمنا ببناء نموذج لنظام حقيقي يُحاكي التصميم الهندسي للسيّارات المُتدفّقة على الطريق السريع بالاعتماد على الهندسة العشوائية لنموذج عملية نقطة بواسون PPP (Poisson Point Process) بكثافة ، ثمّ استخدمنا مُنحنيات المُميّزات الخاصة بنموذج الموجة الحركية (نموذج LWR (Lighthill Whitham Richards)) لإيجاد تابع توزّع كثافة حركة المرور  عند فترات زمنية مُختلفة من الطريق المدروس. فيما بعد، قُمنا بتشكيل صيغة رياضية لحساب القيمة المتوسّطة للتداخل عند فترات زمنية مُختلفة من الطريق. تمّ اختبار النظام باستخدام برنامج MATLAB. تمكّنا في نهاية البحث من إثبات فعّالية طريقة المُميّزات في التنبّؤ بتابع توزّع كثافة حركة المرور وبالتالي معرفة السلوك الزمني للتداخل ولا سيما في حالات سيناريوهات حقيقية على الطريق.